Elements of leadership : lessons from Avatar the Last Airbender - Islam, Sy; Schmidt, Gordon B. (Exploring effective leadership practices through popular culture, 2024)
Leadership literature is dominated by Western paradigms, but what about the lessons of leadership from a cross-cultural perspective? In this highly readable volume, Sy Islam and Gordon B. Schmidt utilise examples from Avatar: The Last Airbender to bring this unique lens of perspective to a range of leadership behaviour themes. The chapters offer research and evidence-based advice on how to improve as a leader on topics such as ethics, balance, power, cross-cultural leadership, female leadership, succession planning, organizational memory, leadership development, mentorship, and creativity. A focus on leadership helps the reader to see that regardless of their current position or role, they can engage in leadership and have impact, whether a current leader or not. Elements of Leadership connects concepts from the franchise to uncover what the reader can achieve within their own leadership process. Exploring Effective Leadership Practices through Popular Culture aims to bring examples, theory and methodology of leadership to life by analyzing academic concepts through popular culture examples that will appeal to a broad range of readers.